Watching, keeping and squeezing time to lose weight: Implications of time-restricted eating in daily life. (1st June 2021) - Bjerre, Natasja; Holm, Lotte; Quist, Jonas Salling; Færch, Kristine; Hempler, Nana Folmann
Abstract: Time-restricted eating (TRE) is a novel intervention that allows eating and drinking within a certain time window and has shown positive effects on body weight in few studies. Weight loss strategies that easily can be integrated into daily life are needed, but knowledge about how TRE affects daily life is lacking. This study examined how individuals having overweight or obesity at high risk of type 2 diabetes performed TRE in daily life, with a focus on how the timing of eating changed the organisation and rhythms of daily activities. Semi-structured interviews were conducted with participants enrolled in a randomised controlled trial studying the effect of a 12-week TRE intervention focusing on a self-selected daily 10-h window between 6 AM and 8 PM. Seventeen participants from the intervention group were interviewed at baseline and end of intervention, and data were analysed using a thematic analysis approach. Participants found TRE simple and appealing due to the unrestricted dietary intake. In general, participants did not change their food preferences and continued to eat three main daily meals. However, participants had to increase their awareness of the time of day, reshuffle ordinary daily activities and plan their intake more carefully. Two participants reported fully adherence every day, whereas all other participants reported one to several episodes of intake outside their window during the 12 weeks. Social evening activities and collective rhythms were largest barriers. Our findings suggest that TRE interventions would benefit from a broader perspective on daily life and an expanded view on families and friends as joint units of intervention. TRE interventions should consider individuals' daily rhythms and help them develop practical solutions to integrating new eating practices. Highlights: First in-depth examination of experiences of performing time-restricted eating. No caloric restrictions make time-restricted eating an appealing weight loss strategy. Reshuffling of daily activities is necessary to perform time-restricted eating. Social life, evening activities and collective rhythms challenge adherence. Time-restricted eating interventions should consider individuals' daily rhythms.